The monitoring of emergent zoonotic pathogens in wild and captive birds in Sarajevo Canton, Bosnia and Herzegovina - Softić, Adis; Nicevic, Melisa; Koro-Spahic, Amira; Terzic, Ilma; Goletic, Sejla; Kapo, Naida; Salkic, Jasna; Omeragic, Jasmin; Goletic, Teufik (Frontiers in Veterinary Science, 2025)
IntroductionWith their remarkable flight capabilities, wild and captive birds play a pivotal role in the global dissemination of zoonotic pathogens including Chlamydia psittaci, Avian Influenza viruses (AIV), Chikungunya virus (CHIKV), Usutu virus (USUV), and West Nile virus (WNV). They function both as hosts and reservoirs responsible for transporting the mentioned infectious agents across vast geographic regions. Additionally, captive birds and birds inhabiting urban environments, particularly in tourist destinations, present significant public health concerns due to facilitated close interactions with humans.MethodsA total of 358 samples originating from fifteen bird species were collected across 21 locations in Sarajevo Canton, over three consecutive years (2022–2024). Upon collection, the samples were subjected to molecular analysis to detect the presence of zoonotic pathogens. For detection of Chlamydia spp., and C. psittaci, real-time PCRs (qPCR) were used following established protocols. Additionally, reverse transcriptase real-time PCR (RT-qPCR) were utilized for the detection of emergent viral pathogens including avian influenza viruses, Chikungunya, Usutu, and West Nile virus.ResultsChlamydia spp. was detected in 29.9% (95% CI: 25.2–34.9) of samples. Further, C. psittaci was identified in 10.3% (95% CI: 5.2–17.7) of positive samples originating from captive birds and birds inhabiting urban environments. One sample (0.3%) originating from a wild bird was positive to West Nile Virus. None of the samples tested positive for Avian Influenza viruses, Chikungunya and Usutu virus.DiscussionThe identification of C. psittaci and West Nile virus highlights the increased likelihood of zoonotic transmission. This underscores the imperative for bolstered biosecurity measures and public health strategies aimed at mitigating the risk associated with both environmental exposure and direct contact, especially in areas characterized by substantial tourist activity.